Efforts to Improve Analytical Thinking Abilities in Mathematics Learning: Problem Solving Learning Model - Guntoro, Erwanto; Tasari; Ruqoyyah, Siti (Journal of Asian Primary Education (JoAPE), 2025)
This study aims to describe (1) the use of problem solving methods by mathematics teachers in debate learning in class VIIIB (2) student responses to the use of problem solving methods in mathematics learning in class VIIIB (3) teacher obstacles that come from students in the use of problem solving methods in mathematics learning in class VIIIB SMP Negeri 3 Numfor Barat. This study uses a quantitative descriptive research design. The subjects of this study are teachers and students. The objects in this study are the use of problem solving methods, student responses, and teacher obstacles. The data collection methods used are observation methods and interview methods. The data in this study were analyzed descriptively quantitatively. The conclusions of this study are (1) the use of problem solving methods has been effective and in accordance with procedures. (2) student responses are mostly positive. (3) the obstacles found by teachers are in terms of students and very limited school facilities. The suggestion of this study is for mathematics teachers to maintain the effectiveness of learning and motivate students more, and for schools to improve learning facilities .